Modifikasi Desain Mesin Pencacah Sampah Daun dan Ranting Kapasitas Input 4 Kg - Adris, Yanuarius; Hariri, Hasan (Indonesian Journal of Engineering and Technology (INAJET), 2024)
Organic waste shredding machine is a machine made to process and destroy various types of organic waste.Variations of organic waste that can be processed include grasses, vegetable remains, fruit skins, leaves, small twigs, and other organic waste. Innovation in science and technology is currently a support for writers in creating works that benefit society. Appropriate equipment is key in turning organic waste into a valuable economic resource. There has been an increase in organic waste treatment equipment. Currently, there is no technology available to process organic waste in the Tonjong area, Tajur Halang. The research methods used in this study consist of problem identification, problem formulation, data collection and Phal &Beitz designer methods. Based on calculations, the specifications of the leaf and twig waste shredding machine are a gasoline fuel motor with a power of 5.5 hp, bearing or shaft diameter Ø20mm and countercapacity of 240 kg / hour Keywords:modify, machine, garbage, organic